2020
DOI: 10.1016/j.ijhcs.2020.102427
|View full text |Cite
|
Sign up to set email alerts
|

Computer games as distraction from PAIN: Effects of hardware and difficulty on pain tolerance and subjective IMMERSION

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…The BCI-N system of this study will address a key limitation of previous EEG neurofeedback interventions, which have mostly relied on a single form of virtual interaction [ 20 , 22 , 24 ]. Studies have shown greater cortical involvement [ 32 ] and pain reduction [ 28 - 31 ] during the interactive engagement with multiple gaming scenarios than with 1 form of virtual interaction. Based on this evidence, we will use a self-developed BCI-N treatment, which consists of 3 interactive virtual scenarios in a goal-directed gaming environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCI-N system of this study will address a key limitation of previous EEG neurofeedback interventions, which have mostly relied on a single form of virtual interaction [ 20 , 22 , 24 ]. Studies have shown greater cortical involvement [ 32 ] and pain reduction [ 28 - 31 ] during the interactive engagement with multiple gaming scenarios than with 1 form of virtual interaction. Based on this evidence, we will use a self-developed BCI-N treatment, which consists of 3 interactive virtual scenarios in a goal-directed gaming environment.…”
Section: Discussionmentioning
confidence: 99%
“…Current BCI-N interventions for both SCI neuropathic pain [ 20 , 22 , 24 ] and chronic pain [ 25 - 27 ] have mostly relied on a single mode of virtual interaction, such as increasing or decreasing the height of a bar presented on a computer screen. However, preliminary evidence suggests that greater pain relief may be achieved from interactive, goal-directed engagement with a gaming environment, in comparison with a single virtual interaction format [ 28 - 31 ]. The increased analgesic effect may be due to the greater cortical involvement, which occurs during engagement with multiple scenarios in a goal-directed manner such as gaming [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current BCI-N interventions for both SCI neuropathic pain [20,22,24] and chronic pain [25][26][27] have mostly relied on a single mode of virtual interaction, such as increasing or decreasing the height of a bar presented on a computer screen. However, preliminary evidence suggests that greater pain relief may be achieved from interactive, goal-directed engagement with a gaming environment, in comparison with a single virtual interaction format [28][29][30][31]. The increased analgesic effect may be due to the greater cortical involvement, which occurs during engagement with multiple scenarios in a goal-directed manner such as gaming [32].…”
Section: Changing Brain Rhythms Reduces Neuropathic Pain Following Scimentioning
confidence: 99%
“…The BCI-N system of this study will address a key limitation of previous EEG neurofeedback interventions, which have mostly relied on a single form of virtual interaction [20,22,24]. Studies have shown greater cortical involvement [32] and pain reduction [28][29][30][31] during the interactive engagement with multiple gaming scenarios than with 1 form of virtual interaction. Based on this evidence, we will use a self-developed BCI-N treatment, which consists of 3 interactive virtual scenarios in a goal-directed gaming environment.…”
Section: Overviewmentioning
confidence: 99%
“…For example, tasks placing a high demand on central executive resources are particularly effective in diverting attention away from pain (6,7). However, studies investigating the effects of increased task difficulty in VR often rely on the manipulation of game settings, such as the speed or number of hit targets, and are therefore likely to be confounded by the participant's gaming experience and motor coordination skills (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%